PEMBACAAN HIZB GHAZÂLÎ DI PONDOK PESANTREN LUQMANIYYAH YOGYAKARTA PERSPEKTIF TEORI SOSIOLOGI PENGETAHUAN KARL MANNHEIM - Rahmanto, Oki Dwi (UIN Sunan Kalijaga Yogyakarta, 2020)
Reading the Qur’an is a form of worship to God which is rewarded for its readers. But in practice, Muslims have another purpose. This research is backed by the meaning by the student in Pesantren of the verses of Qur’an (hizb ghazâlî) that serve as amulets that can grant any wish. As for practice, students are obliged to do the ascetic before doing the hizb reading with fasting for seven consecutive days and read seven times in a day during fasting. The practice of reading (hizb ghazâlî) that exists up to now is not separated from the obligation of students in reading it. Also, the students made this reading as a form of obedience and hoped for the blessing. Using the theory sociology of knowledge by Karl Mannheim’s, this research is expected to reveal the meaning of the students in hizb ghazâlî readings. Karl Mannheim distinguishes between three different meanings in social action, i.e. objective, expressive and documentary meaning. The result of this research is the objective meaning hizb ghazâlî is a form of ijâzah from Na’im. The meaning of expressive is acceptable to serve the wish. The meaning of the documentary, hizb readings can be a thorough cultural practice.